Technology available to the professional adult: INNA and EIRA´s smart products design for professional adults users - Campos-Vallejos, Karen (2019)
The project developed consists of two products called INNA and EIRA that are developed with the same purpose, to facilitate a young professional user  keeping his plants alive inside his home. Both are systems of intelligent care of plants and crops that belong to the same family integrated by factors of the principles of Gestalt of similarity to make them relate in a semantic way: in forms, colors, textures, materials and sizes. These objects use technological resources to generate an ideal environment in which plants can be developed correctly, through alerts that are perceived by all senses. INNA uses Aquaponics which is based on nutrients provided by fish for the good growth of the plant. EIRA specializes in vegetable plants for its future consumption. It uses the principles of Aeroponics which is based on the spraying of nutrients directly to the roots of the plant within a closed air system for the good growth of it. The technology presented in both products is simple and intuitive.